On International Protection Of Minorities; Aspects Of Minorities Protection By Albanian Legislation - Reci, Senada; Zefi, Luljeta (European Scientific Journal, ESJ, 2016)
Minorities are part of the people living in a country and being not part of the majority of the population, always have problems relating to the implementation of the rights and fundamental freedoms to them. Filling this vacuum is internationally seen the Framework Convention for the protection of minorities, which sets targets to be achieved by States and its implementation is provided primarily by the measures taken on the national law and secondarily by bilateral agreements since its provisions are not directly applicable. There are also some other international acts of the Council of Europe that sanction rights for minorities. But this paper devotes attention to Albanian legislation and its commitments to enforce the rights and protection of minorities, especially in the context of the integration process in the EU, where the approach of the standards of the acquis for minorities is the focus of monitoring alongside the fundamental human rights and freedoms from the European Commission. EC has introduced the issue of minorities in the Albanian legislation with problems and situation outside the framework of legal protection because of the vacuum of a legal act for minorities, and this paper aims to present some aspects of the problem reflected in its analysis.